The Empowerment of Grade VI Elementary School Students in Having Compulsory Prayer by Implementing The Strategy of Modeling The Way (Action Research in SD Negeri Sidorejo Kidul 02, Tingkir District, Salatiga Regency, Central Java Province) - Sunarso, Ali (Elementary School Teacher, 2017)
through The Way model and can give contribution to the science and technology development, especially in religion education and can be a new theory about the improvements of the grade VI students’ active in improving the skills to do the compulsory prayer movement. The research result gained is influenced by two main factors, which are from the students themselves, especially on the owned skills and factor from outside of the students or environmental factor, like learning motivation and attention, attitude and learning habit, diligence, economical social, physical factor and others. The discussion results in this research included 3 things; they were action, activity, and students’ skill in doing compulsory prayers. At the beginning condition, teaching of compulsory prayers in grade VI students in IV SD Negeri Sidorejo Kidul 02 did not use the strategy of modeling the way. In cycle I used the strategy of modeling the way without guideline from the teacher. Then, continued by cycle II used the strategy of modeling the way with the teacher’s guideline. It was aimed at combining the method used to make the students more understand.